Synthesis and Biodistribution of [11C]Adenosine 5′-Monophosphate ([11C]AMP) - Mathews, William B.; Nakamoto, Yuji; Abraham, Edward H.; Scheffel, Ursula; Hilton, John; Ravert, Hayden T.; Tatsumi, Mitsuaki; Rauseo, Paige A.; Traughber, Bryan J.; Salikhova, Anna Y.; Dannals, Robert F.; Wahl, Richard L. (Molecular imaging and biology, 2005)
Imaging purine receptors and adenylate biodistribution in vivo may be of clinical importance not only for the investigation of normal adenylate metabolism but also in pathological conditions where adenylate uptake and/or release from certain tissues and organs may be altered, such as some types of cancer. In order to develop a tracer for positron emission tomography (PET) that would not be subject to loss of its radioisotope, adenosine 5'-monophosphate (AMP) was intrinsically labeled at the C-8 position with carbon-11. [11C]AMP was synthesized by reacting 5-amino-1-beta-D-ribofuranosylimidazole-4-carboxamidine-5'-phosphate with [11C]formaldehyde. The metabolism of [11C]AMP in human blood was determined in vitro both in the presence and absence of dipyridamole. The ex vivo biodistribution of [11C]AMP and its in vivo dosimetry were determined in normal mice. The effect of dipyridamole on the distribution of [11C]AMP in mice was also determined. [11C]AMP was reliably synthesized in 34 minutes (n = 7) with an average radiochemical yield of 2.4% and an average specific activity of 90.10 GBq/micromol (2435 mCi/micromol) at end of synthesis. In normal mice, the highest uptake of [11C]AMP was in the lungs, blood, and heart. The ex vivo mouse experiments showed that the uptake of 11C radiotracer in the lungs at 60 minutes postinjection was significantly lower for dipyridamole-treated animals than controls. Dosimetry showed that the critical organs for radiation dose burden are kidneys and bladder. Treatment with dipyridamole blocked the red blood cell uptake of extracellular adenosine and therefore its subsequent intracellular conversion to ATP. The biodistribution studies indicate that the tracer has substantial accumulation in the kidneys, lungs, heart, and blood. [11C]AMP is promising as a PET-imaging agent to trace adenylate biology in vivo.